2013
DOI: 10.1007/s13369-013-0602-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of Film Hole Irrigation on Borders for Water Saving and Sunflower Production

Abstract: Film hole irrigation is relatively reported efficient irrigation technique amongst the others by Chinese's researchers. Film hole irrigation refers to bordered field completely covered with plastic sheet having holes of equal sizes through which seedlings come out. Field experiments were conducted at Postgraduate Agriculture Research Station to check its effectiveness and performance in terms of advance rate on sunflower crop for various sized borders having Fine Sandy Loam soil. Tube well irrigation water was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The change rate of soil nitrate nitrogen with conversion time irrigation methods and influencing factors of film-hole irrigation were comprehensively evaluated from the soil water and nutrient perspectives, and the numerical simulation of soil water and nitrogen migration and transformation under the conditions of water and fertilizer absorption by film-hole irrigated crops was studied to reveal the patterns of soil water and nitrogen migration and transformation (Saeed and Mahmood, 2013;Mailhol et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change rate of soil nitrate nitrogen with conversion time irrigation methods and influencing factors of film-hole irrigation were comprehensively evaluated from the soil water and nutrient perspectives, and the numerical simulation of soil water and nitrogen migration and transformation under the conditions of water and fertilizer absorption by film-hole irrigated crops was studied to reveal the patterns of soil water and nitrogen migration and transformation (Saeed and Mahmood, 2013;Mailhol et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Outside of China, Muhammad Saeed increased sunflower yield and quality through membrane irrigation. Compared with conventional irrigation, film-hole irrigation saved 37-45% of the water used, and sunflower yield increased by 23-30% compared with that under conventional irrigation (Saeed and Mahmood, 2013). Unlike other irrigation methods, film-hole irrigation used a thin layer of water on the film, which penetrated into the roots of crops through film holes.…”
Section: O T S C L é Smentioning
confidence: 99%
“…Liu et al [13] showed that PFM led to the volume moisture content increased by 3.5% at depths of 0-20 cm in winter wheat farmland. Compared with conventional surface irrigation, FHI can save 37%-45% water and increase sunflower yield by 23%-30% [14] . Several fields and laboratory experiments have been carried out to study the effects of influence factors (e.g., soil texture, soil bulk density, film hole diameter, sediment content.)…”
Section: Introduction mentioning
confidence: 99%
“…Because the water flows on the film and the flow speed is fast, this reduces the deep water leakage at the head of the plot and improves the uniformity of irrigation water. At the same time, the water accumulating on the film directly penetrates into the root zone of the crop through the film hole (emergence hole or special irrigation hole), which improves the irrigation water utilization efficiency (Saeed and Mahmood, 2013). FHI combines many advantages of dry farming and surface irrigation.…”
Section: Introductionmentioning
confidence: 99%